2019
DOI: 10.3390/f10060523
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Forest Ecosystems across the Vertical Edge of the Mid-Latitude Ecotone Using the BioGeoChemistry Management Model (BGC-MAN)

Abstract: The mid-latitude ecotone (MLE)—a transition zone between boreal and temperate forests, which includes the regions of Northeast Asia around 30°–60° N latitudes—delivers different ecosystem functions depending on different management activities. In this study, we assessed forest volume and net primary productivity changes in the MLE of Northeast Asia under different ecological characteristics, as well as various current management activities, using the BioGeoChemistry Management Model (BGC-MAN). We selected five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…The NPP calculated in this study was higher than that reported in previous studies (4.30-6.70 tC ha −1 [55,56], and 7.99 ± 0.62 tC ha −1 in 2000s [57]); the values of NPP differed depending on whether the tree was a conifer or broadleaf. In this study, broadleaf forests exhibit a higher mean NPP than conifer forests, which is similar to the results of other studies [58,59]. Additionally, the differences in the NPP were observed among several species; e.g., pine and larch [59,60].…”
Section: Discussionsupporting
confidence: 91%
“…The NPP calculated in this study was higher than that reported in previous studies (4.30-6.70 tC ha −1 [55,56], and 7.99 ± 0.62 tC ha −1 in 2000s [57]); the values of NPP differed depending on whether the tree was a conifer or broadleaf. In this study, broadleaf forests exhibit a higher mean NPP than conifer forests, which is similar to the results of other studies [58,59]. Additionally, the differences in the NPP were observed among several species; e.g., pine and larch [59,60].…”
Section: Discussionsupporting
confidence: 91%
“…This paper has explored the dynamics of GPP and NPP variables in Peninsular Spain, which is located in the mid-latitude ecotone (MLE) [54], the zone between 30 • -60 • latitude that comprises a transition belt between forests (temperate forest in Spain) and drylands. GPP and NPP are variables linked to carbon fluxes and biomass production, which can be used to analyze the ecosystem state.…”
Section: Discussionmentioning
confidence: 99%
“…The study area lies in northern MLR where heavy land degradation and ecological transitions have occurred [1,4]. To identify the overall trend of environmental characteristics, we selected the focusing zone, where the land cover has transitioned from forest to bare land, from where the desert starts (Mongolia) to the end of the bare land (Caspian Sea).…”
Section: Study Areamentioning
confidence: 99%
“…The MLR overlaps the "global dust belt" extending from North Africa to Central and East Asia [2]. Therefore, all countries in MLR are suffered by frequent occurrence of Sand and Dust Storm (SDS) and land degradation driven by various climate, environmental, and socioeconomic factors [3][4][5]. In general, SDS are regarded as global disaster events accompanied by strong winds and sand lifted from desert areas.…”
Section: Introductionmentioning
confidence: 99%